Does an early discharge of a newborn influence the success of the newborn hearing screening in developing countries? A hospital based study - Nermin Hrnčić (Medicinski glasnik, 2019)
Aim: To investigate outcomes of newborn hearing screening (NHS) with transient evoked otoacoustic emissions (TEOAE) depending on the time from the birth to hearing screening. Methods: A prospective study was performed in the Cantonal Hospital Zenica, Bosnia and Herzegovina. The NHS with TEOAE was done before hospital discharge for all infants. The total of 1217 newborns were tested during a six-month period, from 1 st February to 31 st July 2016. The data of 1167 were available for analysis. Those data were divided in four groups depending on the time passed from the birth to hearing screening: Group A (n = 133 newborns, NHS performed in the first 24 hours after birth); group B (n = 294 newborns, NHS performed between 24-36h after birth); group C (n = 184 newborns, NHS performed between 36-48h after birth) and group D (n= 556 newborns, NHS performed later than 48h after birth). Results: Total referral rate was 19.1% (n = 223): for group A 30.1% (n=40), for group B 25.2% (n=74), for group C 19.0% (n=35) and for group D 13.3% (n=74). There was statistically significant difference between groups A and C (p=0.03), between groups A and D (p<0.001) and between groups B and D (p<0.001) in total and in well baby nursery (WBN). Conclusion: The total referral rates in NHS were high because of early post birth discharge of newborns. The NHS should be performed in infants older than 36 hours according to the results in this study.
Keywords: developing countries; hearing loss; neonatal screening; otoacoustic emissions